2015
DOI: 10.1371/journal.pone.0116706
|View full text |Cite|
|
Sign up to set email alerts
|

Nosewitness Identification: Effects of Negative Emotion

Abstract: Every individual has a unique body odor (BO), similar to a fingerprint. In forensic research, identification of culprit BOs has been performed by trained dogs, but not by humans. We introduce the concept of nosewitness identification and present the first experimental results on BO memory in witness situations involving violent crimes. Two experiments indicated that BO associated with male characters in authentic videos could later be identified in BO lineup tests well above chance. Moreover, culprit BO in emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Nonetheless, human chemosignalling research has revealed that stable and temporal features of a sender are communicated through the chemical senses ( Lübke and Pause, 2015 ). Especially, when male and female communication via axillary odor is studied, features of a sender affect various levels in a receiver, e.g., social behavior ( Frumin et al, 2015 ), emotional perception ( Zhou and Chen, 2009 ; Albrecht et al, 2011 ), memory function ( Alho et al, 2015 ), social evaluation ( Mitro et al, 2012 ), attractiveness, and mating preferences ( Wedekind and Füri, 1997 ; Thornhill et al, 2003 ; Havlicek et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, human chemosignalling research has revealed that stable and temporal features of a sender are communicated through the chemical senses ( Lübke and Pause, 2015 ). Especially, when male and female communication via axillary odor is studied, features of a sender affect various levels in a receiver, e.g., social behavior ( Frumin et al, 2015 ), emotional perception ( Zhou and Chen, 2009 ; Albrecht et al, 2011 ), memory function ( Alho et al, 2015 ), social evaluation ( Mitro et al, 2012 ), attractiveness, and mating preferences ( Wedekind and Füri, 1997 ; Thornhill et al, 2003 ; Havlicek et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that the performance levels of dogs are typically in the range of 75–90% correct ( Settle et al, 1994 ; Schoon, 1996 ; Marchal et al, 2016 ). Only one study so far has investigated human identification of BO in a forensic set up ( Alho et al, 2015 ; see below).…”
Section: Introductionmentioning
confidence: 99%
“…Donors were instructed to refrain Do masculine men smell better? from using fragrant hygiene products (e.g., perfume, body lotions), smoking, eating spicy foods, garlic, and drinking alcohol, the day before the body odor sampling and until the end of the sampling, in order to avoid alterations of their natural body odor (Alho et al 2015).…”
Section: Sampling Of Donors' Body Odormentioning
confidence: 99%
“…After they had put on the white cotton t-shirt supplied, donors could also wear their personal clothes if they were clean (and fragrance free). Body odors were collected on the cotton pads attached to their armpits (Alho et al 2015;Mitro et al 2012). Donors wore the t-shirts for periods of 4 hours.…”
Section: Sampling Of Donors' Body Odormentioning
confidence: 99%